Neuroprotective effect of tocotrienol-rich fraction and a-tocopherol of vitamin E against glutamate toxicity in neuronal cells and astrocytes - Selvaraju, Thilaga Rati (2015)
Vitamin E is a fat-soluble antioxidant consisting of tocopherol and tocotrienol. The tocotrienol-rich fraction (TRF) palm oil extract comprises 25% α-tocopherol (α- TCP) and 75% tocotrienols. TRF has been shown to possess potent antioxidant, antiinflammatory,anti-cancer, neuroprotective, and cholesterol-lowering activities. Glutamate is the main excitatory amino acid neurotransmitter in mammalian central nervous systems; it can be excitotoxic and has been suggested to play a key role in neurodegenerative disorders such as Parkinson’s and Alzheimer’s disease. In this study, the effects of vitamin E when supplemented before (pre-treatment) and after (post-treatment) glutamate insult were elucidated in neuronal and astrocyte cell lines. The neuroprotective effect of TRF and α-TCP were investigated. Glutamatemediated cytotoxicity was diminished by pre- and post-treatment of TRF and α-TCP.Vitamin E acted as a potent antioxidant agent in recovering mitochondrial injury from elevated oxidative stress, and cells exhibited better survival following glutamate toxicity. Quantitative morphological studies were also conducted via an apoptosis detection kit using flow cytometric analysis. Pre- and post-treatment with TRF and α-TCP led to better survival and lower cell death rates following glutamate neurotoxicity. The flow cytometry morphological findings were validated by scanning electron microscopy analysis. Cell cycle analysis was also performed using an RNAse-propidium iodide assay. The presence of glutamate in the nerve cells caused DNA or protein damage and chromatin destruction; manipulating these nerve cells to re-enter the cell cycle promoted repair of the damage. Supplementation of TRF and α-TCP enhanced the DNA repair process, with higher numbers of nerve cells accumulating in the S and G2/M phases, indicating active replication and repair of the DNA damage that had occurred during the previous cell cycle. In both TRF and α-TCP pre- and post-treatment groups, glutamate-injured cells exhibited significant reductions in concentrations of the lipid peroxidation biomarker malondialdehyde. Ferric reducing antioxidant power (FRAP) assay was employed to determine the total antioxidant power in the cells. There was significantly increased antioxidant capacity in the cells treated with TRF or α-TCP as compared to glutamate-treated cells, which indicated good neuroprotection. Exposure to glutamate also reduced the concentrations of glutathione, superoxide dismutase, and catalase, important natural antioxidants synthesized in neurons and astrocytes. Both pre- and post-treatment of vitamin E markedly increased antioxidant activity. Subsequently, the expression of traumatic brain injury markers for neuron-specific enolase (NSE) and S100 calcium-binding protein B (S100 β) were elucidated using real-time PCR. The results revealed the downregulation of NSE and S100B upon glutamate challenge in neuronal cells and astrocytes following treatment with different concentrations of TRF and α-TCP, a sign of the recovery process. Human apoptosis quantitative PCR array analysis determined that post-treatment with 200 ng/mL TRF and α-TCP upregulated the anti-apoptotic genes and downregulated the pro-apoptotic genes in both the neuronal and astrocyte cell lines. In conclusion, TRF and α-TCP have protective and recovery properties against glutamate toxicity in neuronal cells and astrocytes. From the average value calculation, TRF preceded α-TCP in neuroprotection against glutamate insult in both astrocytes and neuronal cells. Hence, the present study can serve as a platform for further studies on the effects of TRF and α-TCP, as they could be developed into potential treatment agents for neurodegenerative diseases.